STUDENTS’ PERCEPTION OF PRE-SERVICE TEACHERS’ COMPETENCE AND THEIR READING ACHIEVEMENT DURING PANDEMIC COVID 19 - Maulidifi Ajrin Karimata; Dwi Fita Heriyawati; Junaidi Mistar (Universitas Brawijaya, 2022)
In April until December is one of the schedule for pre-service teachers’ to do practice teaching in school. Because of pandemic era, their activities were slightly disrupted. Starting from schools that cannot accept pre-service teachers’ to doing practice teaching due to online learning to various reasons given by the school to pre-services teacher. The objective of this research was to find out the correlation between students’ perception of pre-service teachers' competence and their reading achievement. This research was classified into correlational research design. The participants of this research were 58 students in eleventh grade at SMK Negeri 1 Lamongan. This research were questionnaire and test (reading achievement test). The test and questionnaire were analyzed by looking at the total score from the highest to the lowest, and the result of correlation was interpreted by looking the significance criteria. This research indicate that the correlation coefficient is negligible with a value of -.069 and the significant value shows .608. At sig. 2-tailed shows .608 > .05 which means that there is no significant correlation. By realizing and considering the importance of pre-service teachers to provide good examples of character, behavior, motivation, and attitude towards students and the need for further studies on the same or other factors related to reading comprehension skills.